ELectroless Ni-W-P Alloy Deposition on Mild Steel Using Lawsone Isolated from Lawsonia inermis Linn Leaf Acts as Complexing Agent - H. Asia Thabassoom; J. Felicita Florence (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
Electroless plating, sometimes referred to as chemical plating or auto-catalytic plating, is a non-galvanic plating method that incorporates numerous continuous chemical processes in an aqueous solution without the usage of external electrical power. Electroless coatings are used in many industries nowadays due to their good properties, such as corrosion and wear resistance, hardness and uniform thickness. Nickel sulphate and Sodium tungstate was used as Nickel and tungsten sources respectively, Sodium hypophosphite was used as a reducing agent. The effect of Lawsone isolated from Lawsonia inermis Linn leaf extract and found that complexing agent Sodium citrate was replaced by Lawsone which enhances plating properties. In order to characterise Ni-W-P surfaces, SEM, EDAX and XRD methods were used. We looked at the Ni-W-P corrosion resistance behaviour as well as electrochemical techniques such as potentiodynamic polarisation curve and electrochemical impedance spectroscopy. Corrosion tests show that electroless Ni-W-P coatings deposited in all conditions significantly improve mild steel corrosion resistance. Metal that is electrolessly deposited has good corrosion resistance.